An integrative redescription of Echiniscus quadrispinosus quadrispinosus Richters, 1902 (Heterotardigrada, Echiniscidae) from the terra typica in Taunus Mountain Range (Europe; Germany) - Kaczmarek, Łukasz; Kayastha, Pushpalata; Gawlak, Magdalena; Mioduchowska, Monika; Roszkowska, Milena (European Journal of Taxonomy, 2022)
In the present study, we used an integrative taxonomy approach to redescribe a population of Echiniscus quadrispinosus quadrispinosus Richters, 1902 from the neotype locality in the Taunus Mountain Range (Germany). We found clear differences in the chaetotaxy formula between the life stages of E. q. quadrispinosus. The body appendages B are, in general, absent in juveniles. Moreover, in larvae all body lateral appendages, except for E, are absent. We also obtained DNA sequences of 18S rRNA, 28S rRNA, ITS-2, and COI of E. q. quadrispinosus from the neotype locality and three Norwegian populations. Comparison with the sequences available in GenBank showed low genetic differences between the neotypic population and specimens from other localities. Therefore, we decided to establish our specimens from Taunus Mountain Range as neotype and paraneotypes of E. q. quadrispinosus. We also discussed and amended the taxonomic status of three subspecies E. q. brachyspinosus Bartoš, 1934, E. q. cribrosus Murray, 1907 and E. q. fissispinosus Murray, 1907 and established them as junior synonyms of E. q. quadrispinosus. Finally, we also confirmed E. lichenorum Maucci, 1983 as a valid species, clearly different from E. q. quadrispinosus.